ON SN-SPACES - H. Majeed , Abdul-Rahman; AL-Bayati, Jalal H. Hussein (Iraqi Journal of Science, 2022)
The aim of this paper is to introduce and study the concept of SN-spaces via the notation of simply-open sets as well as to investigate their relationship to other topological spaces and give some of its properties.